The relation of step length to MRI detected structural damage in the patellofemoral joint: The Multicenter Osteoarthritis Study - Stefanik, Joshua J. (Arthritis Care Res (Hoboken), 2016)
OBJECTIVE: Investigate the relation of step length to the sex-specific prevalence and worsening of MRI-detected structural damage in the patellofemoral joint (PFJ) among a cohort of older women and men with or at risk for knee osteoarthritis (OA). METHODS: The Multicenter Osteoarthritis (MOST) Study is a cohort study of persons aged 50-79 years with or at risk for knee OA. Step length was assessed using the GAITRite system at the 60-month visit and cartilage damage and bone marrow lesions (BMLs) were graded on MRI at the 60 and 84-month visits. We divided step length into sex-specific quintiles and examined the relation of step length to the prevalence and worsening of cartilage damage and BMLs in the PFJ using logistic regression, adjusting for age, body mass index (BMI), leg length and tibiofemoral joint structural damage. RESULTS: 4094 and 4083 PFJ subregions from 1053 knees were studied for the cartilage and BML analyses, respectively. Mean age was 65.6 (±8.1) years and mean BMI was 29.1 (±4.7) kg/m(2); 62% were female. In women, compared to those with the shortest step length those with the longest step length had 0.62 (0.43, 0.88) and 0.59 (0.40, 0.87) times the odds of cartilage damage and BMLs, respectively. There was no cross-sectional association in men, and no longitudinal association in either sex. CONCLUSION: Women with PFJ structural damage may adapt their gait by shortening their step length, but this may not be sufficient to reduce risk of worsening damage over time.